Parallel processing of whole words and morphemes in visual word recognition. - Beyersmann, Elisabeth; Coltheart, Max; Castles, Anne (Quarterly Journal of Experimental Psychology, 2012)
Models of morphological processing make different predictions about whether morphologically complex written words are initially decomposed and recognized on the basis of their morphemic subunits or whether they can directly be accessed as whole words and at what point semantics begin to influence morphological processing. In this study, we used unprimed and masked primed lexical decision to compare truly suffixed (darkest) and pseudosuffixed words (glossary) with within-boundary (d ra kest/g ol ssary) to across-boundary (dar ek st/glos as ry) letter transpositions. Significant transposed-letter similarity effects were found independently of the morphological position of the letter transposition, demonstrating that, in English, morphologically complex whole-word representations can be directly accessed at initial word processing stages. In a third masked primed lexical decision experiment, the same materials were used in the context of stem target priming, and it was found that truly suffixed primes facilitate the recognition of their stem-target (darkest–DARK) to the same extent as pseudosuffixed primes (glossary–GLOSS), which is consistent with theories of early morpho-orthographic decomposition. Taken together, our findings provide evidence for both whole-word access and morphological decomposition at initial stages of visual word recognition and are discussed in the context of a hybrid account.